Perancangan Ulang Tata Letak Fasilitas Lantai Produksi Batik Tulis Pewarna Alam - Nancy Oktyajati; Diyah Dwi Nugraheni; Sri Mayasari; Sri Purwanti (Program Studi Teknik Industri Universitas Setia Budi, 2022)
Batik is an indigenous Indonesian product that is recognized worldwide. One way to preserve and develop batik culture is increasing the batik business productivity effectively, economically, and safely. Increasing the productivity of the batik industry can be realized by minimizing production costs. Reduction of operational costs can be done by designing the layout of the facility. Redesigning the layout and facilities is closely related to the design of the floor production as an object. Layout planning is a way of managing existing facilities on the production floor so that production can run smoothly. This study, aims to redesign the facilities on the floor production at SME Batik Natural Jarum so that they have a more efficient material flow. Arrangements are made for all work stations: raw material storage, production areas, and finishing areas. The purpose of this facility redesign is make the movement of materials run smoothly and reduced material handling costs. The method used in this research is Systematic Layout Planning (SLP). The results of the proposed layout redesign are a reduction in material handling distances and material handling costs by 8%.